The sulfurous compounds consisting of hydrocarbon fuels - Медвєдєва, Т.В.; Іванов, С.В.; Бойченко, С.В. (Proceedings of National Aviation University (archive), 2004)
The sulfurous compounds have been studied and their negative influence on operation properties of the oil and products of its processing have been described. Basic methods of definition of the hydrogen sulphide, mercaptans in the hydrocarbon fuels have been shown.